Academic Help-Seeking Behavior of University Students in the EFL Classroom - Zulqadri, Muhammad Fachri; Mahmud, Murni; Weda, Sukardi (International Journal of Language, Education, and Literature, 2026)
This research investigates the academic help-seeking behavior of university students in EFL classroom, focusing on lecturers’ perceptions, the impacts of help-seeking, and the factors that influence students’ willingness to seek assistance. This study is grounded in the understanding that help-seeking is an essential self-regulated learning strategy that supports students in overcoming academic challenges, particularly in complex areas of English language learning. Using a qualitative descriptive approach, data were collected through interviews and focus group discussions with an English lecturer and six sixth-semester students at Universitas Islam Negeri Makassar. The findings reveal that students tend to avoid direct help-seeking from lecturers due to fear of judgment, embarrassment, and cultural norms that associate asking for help with weakness. Instead, they rely more on peers, internet sources, and AI tools. Lecturers perceive this behavior as a challenge that can hinder deep understanding and timely clarification. Nonetheless, when students do seek help, it positively impacts their learning by improving comprehension, boosting confidence, fostering engagement, and enhancing academic performance. The study also identifies several factors influencing help-seeking behavior, including self-efficacy, prior experiences, peer perception, cultural stigma, availability of academic support systems, and lecturer student relationships. In conclusion, academic help-seeking plays a crucial role in supporting EFL students’ language development. Creating a supportive learning environment, normalizing help-seeking, and improving access to academic resources are essential for encouraging students to seek assistance as a productive and strategic learning behavior.